Left ventricular strain patterns and their relationships with cardiac biomarkers in hypertrophic cardiomyopathy patients with preserved left ventricular ejection fraction - Zhang, Lisha; Wan, Yixuan; He, Bo; Wang, Lei; Zhu, Dongyong; Gao, Fabao (Frontiers in Cardiovascular Medicine, 2022)
Aims To assess left ventricular (LV) function in hypertrophic cardiomyopathy (HCM) patients with preserved left ventricular ejection fraction (LVEF) by LV strain patterns based on cardiac magnetic resonance feature tracking (CMR-FT) and to explore the relationships between LV strain patterns and cardiac biomarkers in these patients such as cardiac troponin (cTnT) and N-terminal prohormone of the brain natriuretic peptide (NT-proBNP). Methods A total of 64 HCM patients with preserved LVEF and 33 healthy people were included in this study. All subjects underwent contrast-enhanced CMR and all patients took the blood test for cTnT and NT-proBNP during hospitalization. Results Despite the absence of significant difference in LVEF between HCM patients and healthy controls, almost all global and segmental strains in radial, circumferential and longitudinal directions in HCM group deteriorated significantly as compared to controls (p < 0.05). Moreover, some global and segmental strains correlated significantly with NT-proBNP and cTnT in HCM patients and the best correlations were global radial strain (GRS) (r = - 0.553, p < 0.001) and mid-ventricular radial strain (MRS) (r= - 0.582, p < 0.001), respectively, with the moderate correlation. The receiver operating characteristic (ROC) results showed that among the LV deformation parameters, GRS [area under curve (AUC), 0.76; sensitivity, 0.49; specificity, 1.00] and MRS (AUC, 0.81; sensitivity, 0.77; specificity, 0.79) demonstrated greater diagnostic accuracy to predict elevated NT-proBNP and abnormal cTnT, respectively. Their cut-off values were 21.17% and 20.94%, respectively. Finally, all global strains demonstrated moderate, good and excellent intra- and inter-observer reproducibility. Conclusion LV strain patterns can be used to assess the subclinical cardiac function of HCM patients on its merit of being more sensitive than LVEF. In addition, LV strain patterns can detect serious HCM patients and may be helpful to noninvasively predicate elevated NT-proBNP and cTnT. Keywords hypertrophic cardiomyopathy; cardiac magnetic resonance feature tracking; strain; cardiac troponin T; N-terminal prohormone of the brain natriuretic peptide.